2019
DOI: 10.1007/s10815-019-01484-z
|View full text |Cite
|
Sign up to set email alerts
|

Maternal serum levels of angiogenic markers and markers of placentation in pregnancies conceived with fresh and vitrified-warmed blastocyst transfer

Abstract: The aim of the study was to compare the levels of angiogenic markers and markers of placentation between pregnancies conceived with fresh (ET) and vitrified-warmed blastocyst transfer (FET). Methods Women with singleton pregnancies resulting from fresh ET or FET during the period between 2013 and 2017 were included in this prospective observational study. Fresh ET was performed in a stimulated and FET in natural cycle. At 6-7 weeks of gestation, after ultrasound confirmation of a single gestational sac with a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 34 publications
1
1
0
Order By: Relevance
“…Some data suggest no difference in PAPP-A levels in pregnancies resulting from fresh embryo transfer (ET), FET, or spontaneous conception [30], and other studies have shown lower first trimester maternal serum PAPP-A levels in pregnancies conceived as a result of either fresh ET or FET as compared with spontaneous pregnancies [31][32][33][34][35][36][37], which may support the concept of suboptimal placentation leading to related pregnancy complications, particularly in cases of fresh embryo transfers. In a prospective observational study comparing levels of angiogenic markers and markers of early placentation in maternal serum among women who conceived via fresh versus frozen ET, women who achieved pregnancy via FET had higher serum levels of PAPP-A than those who achieved pregnancy via fresh ET, consistent with previous clinical data suggesting more favorable obstetric outcomes with FET than fresh ET [38]. Interestingly, one study showed no correlation between blastocyst morphology parameters and first trimester maternal serum PAPP-A levels in ongoing pregnancies, which were defined as pregnancies which progressed to at least beyond 13 weeks of gestation in that study [39].…”
Section: Discussionsupporting
confidence: 82%
“…Some data suggest no difference in PAPP-A levels in pregnancies resulting from fresh embryo transfer (ET), FET, or spontaneous conception [30], and other studies have shown lower first trimester maternal serum PAPP-A levels in pregnancies conceived as a result of either fresh ET or FET as compared with spontaneous pregnancies [31][32][33][34][35][36][37], which may support the concept of suboptimal placentation leading to related pregnancy complications, particularly in cases of fresh embryo transfers. In a prospective observational study comparing levels of angiogenic markers and markers of early placentation in maternal serum among women who conceived via fresh versus frozen ET, women who achieved pregnancy via FET had higher serum levels of PAPP-A than those who achieved pregnancy via fresh ET, consistent with previous clinical data suggesting more favorable obstetric outcomes with FET than fresh ET [38]. Interestingly, one study showed no correlation between blastocyst morphology parameters and first trimester maternal serum PAPP-A levels in ongoing pregnancies, which were defined as pregnancies which progressed to at least beyond 13 weeks of gestation in that study [39].…”
Section: Discussionsupporting
confidence: 82%
“…Transferring blastocysts is therefore perceived as the best option for elective single-embryo transfer (eSET), by reducing the risk of multiple pregnancies (3,4) without compromising live birth rates. With advances in cryopreservation techniques, improved implantation rates have been achieved, and pregnancy rates after frozen embryo transfer (FET) are at least comparable with those after the transfer of fresh IVF embryos (5). How to select single-blastocyst transfer for FET to reduce the time to successful pregnancy is very important.…”
Section: Introductionmentioning
confidence: 99%